As múltiplas faces do outro/Outro em Lacan entre o amor, o desejo e o gozo - Moreira, Adriano da Silva (2017)
The problem of alterity runs through the entire Lacanian work and our proposal of work consists in investigating the question by showing how it establishes a complex relationship between love, desire and joy. Lacan approaches alterity through the concept of the other/Other, a concept that goes through several moments, namely: 1) the other as similar to oneself; 2) the Other as the place of the unconscious; 3) the other as an object (small ) cause of desire; 4) the other of the social bondand, and finally, 5) the Other as Heteros, the Other sex. Our proposal is to figure out how the other/Other impacts the subject in a relationship that occurs with love, desire or joy.